Analysis tool for bioclimatic design strategies in hot humid climates. (February 2019) - Attia, Shady; Lacombe, Théo; Rakotondramiarana, Hery Tiana; Garde, François; Roshan, GholamReza
Highlights: We developed a climate zoning method based on solar radiation, altitude & temperature. ASHRAE adaptive comfort model is the best available comfort model. Natural comfort potential varies from 22 in Antananarivo to 45% in Toamasina. We developed a bioclimatic analysis tool for cities in hot-humid climates. Abstract: Housing projects design in cities should be based on an understanding of the urban local climate; selection of fit-to-purpose thermal comfort models and implementation corresponding design guidelines and best practices. In this context, we developed an analysis tool for bioclimatic design recommendations for architects in Madagascar. The aim of this tool is to support the decision-making process of architects and urban planners by proposing environmental design guidelines for Antananarivo and Toamasina, the two largest cities on the island. Firstly, we performed a climate zoning of the island based on altitude, solar irradiation and dry bulb temperature. Secondly, we developed a bioclimatic analysis based on temperature and humidity levels. The results show that ASHRAE adaptive comfort model is the best model for both cities because it can tolerate higher humidity limits of up to 80% or more. The natural comfort potential varies from 22 in Antananarivo to 45% in Toamasina. Results can be used to create informative bioclimatic analysis visualisations to better assess climate and determine thermal comfort models for other cities in hot-humid climates. The capabilities of the tool allow architects and urban planners to better understand the climate and propose practical design guidance.